Representation of psychological problems in the research of V. N. Myasischev - Sokolova, Emilia A. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The study revealed the representation of psychological problems in the work of V. N. Myasischev. The purpose of the study is to establish understanding of psychological problems by V. N. Myasischev. The method of research was the theoretical analysis of the literature by interpreting the texts of a number of works by V. N. Myasischev. Prerequisites and conditions of their origin, components of psychological problems, personality and psychological problems of the interaction, the dynamics of the emergence and existence of psychological problems are being shown. Results of the study can be used by practical psychologists working with clients.
Keywords: pathogenic situation; neurosis; a psychological problem; experience; subject; personality